Identification of Phytochemicals Compound On the Ethanol Extract â€Žof Banana Peel Musa Balbisiana Colla â€œKepok Putihâ€ and Musa X â€ŽCorniculata Lour. â€œTandukâ€â€Ž - Wardati, Fauchil; Fitriahani, Feby; Laily, Ainun â€Ž Nikmati (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2020)
Indonesia is the largest banana producer in Asia and each year continues to increase its production. The number of banana production in Indonesia reached 4,177,155 tons in 2003 and increased continuously to 6,373,533 tons in 2009. The abundance of banana peel is not comparable with the utilization of a banana peel in the society which has so far not been processed much apart from being animal feed. Two types of bananas that are often processed but the peels have not been optimally utilized yet are â€œkepok putihâ€ and â€œtandukâ€. Banana peel of â€œkepok kuningâ€ extract contains alkaloids, flavonoids, quinones, saponins and tannins. However, the phytochemical compounds of banana peel â€œkepok putihâ€ and â€œtandukâ€ have not been widely studied. Thus, this research aims to identify the phytochemical compounds from banana peel of â€œkepok putihâ€ and â€œtandukâ€. The extraction method which used in this experiment was the maceration method using 96 % ethanol solvent. Based on the test results, which may be obtained, it is known that the ethanol extract of banana peel â€œkepok putihâ€ contains flavonoids, tannins,Â alkaloids, while â€œtandukâ€ contains flavonoids, saponins, tannins, and alkaloids